RENCANA TATA RUANG PERKOTAAN BERDASARKAN UNDANG-UNDANG NOMOR : 26 TAHUN 2007 - Nurahim Rasudin (JIP ( Jurnal Industri dan Perkotaan ), 2008)
Settlement and construction of space has have jurisdiction since regulation ofsettlement of space number 24/1992. with space regulation, we hope that civilization materialized,compfortable, productive and sustainable. But, the most of frame above, not solid yet. Withthe result that, we need some regulations to accommodate. In year 2007, the government wascreate regulation number 26/2007. with this regulation can making regulation of space work.It will be run if all of civil society and stake holder involve in.